News about the painting profession in Lima (1830-1879) - Holguín Valdez, Anthony (2021)
The historiographical review of the Lima painter’s work in the first decades of the Republican period and in the present time has lacked adequate consideration. In this regard, the issue of the creation of a painting academy and the experiences of the artist’s studio needs to be carefully analysed on the basis of new primary information. Then the present study does not aim to establish absolute truth, but to present the reflections of some of its protagonists and to provide documentary sources on the forgotten painters’ guild from 1830 to 1879, with the aim of opening up new debates on the pictorial context in the Republican period.